Comparison of Selective Parenchymal Clamping to Hilar Clamping During Robotic-assisted Laparoscopic Partial Nephrectomy - Hsi, Ryan S. (Urology, 2013)
OBJECTIVE: To compare perioperative outcomes after robotic-assisted laparoscopic partial nephrectomy (RALPN) with hilar clamping vs parenchymal clamping. METHODS: A retrospective, single-institution review of the patients undergoing RALPN with hilar or parenchymal clamping was performed. Associations between perioperative factors and clinicopathologic outcomes were determined using the t test, Fisher’s exact test, and multivariate linear regression. RESULTS: In 51 patients undergoing RALPN, 36 (71%) and 15 (29%) were performed with hilar and parenchymal clamping, respectively. Median tumor diameter was 2.8 cm for both groups (range, 1.1–6.1; P =.93). Tumor complexity by nephrometry score was mild (69% vs 80%), moderate (29% vs 20%), and high (2% vs 0%) in the respective groups (P =.65). Operative time was significantly shorter in the parenchymal clamp group (median 245 vs 320 minutes; P <.0001). There was no difference in blood loss and need for transfusion. On multivariate analysis, hilar clamping (P <.01), higher body mass index (P =.01), and higher complexity tumors (P =.02) were significantly associated with longer operative times. The parenchymal clamp group had better preservation of immediate postoperative glomerular filtration rate (GFR) from baseline to postoperative day 2 (median ΔGFR 0 vs −18 mL/min/1.73 m(2), P =.02). These differences from baseline did not persist (median ΔGFR −6 vs −7 mL/min/1.73 m(2), P =.35) at a median follow-up of 6.6 months. Final pathology determination of malignancy (P =.51) and positive margin rates (P =.26) were similar in both groups. CONCLUSION: Compared with hilar clamping, selective regional ischemia with the parenchymal clamp for mild-moderately complex tumors is feasible and safe during RALPN. Parenchymal clamping is associated with enhanced immediate preservation of GFR and shorter operative times.